(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aim of this research is to study the effect of the economic value added in evaluating the financial Performance of the Islamic Banks, The researcher followed The procedure of the application study Through extracting the incoming data through both the list of the financial center and the income list that impressed by applying the entrance of the economic value added, The research sample includes the private Islamic banks listed on the Damascus Stock Exchange, which numbered 3 banks, represented by: Syria International Islamic Bank, Al Baraka Islamic Bank, and Sham Islamic Bank, which spanned years. The study is from 2011 through 2018, There is an effect of the application of the indicator of the economical value added in evaluating the performance and There are intrinsic differences between using the traditional pointers of the financial analysis and the economic value added in evaluating the performance of the Islamic Banks included In Damascus market of the Paper Currency.